ANALISIS PENGARUH INFLASI, KURS TUKAR, DAN JUMLAH PRODUKSI TERHADAP EKSPOR KOMODITI KARET DI INDONESIA - Titah Nisfulaila Noviana; Sudarti Sudarti (Jurnal Ilmu Ekonomi JIE, 2018)
In general, developing countries like Indonesia tend to conduct export activities. Eksport provide many benefits to the indonesia such as increasing foreign exchange of  a country. The aim of this study was to determine the effect of inflation, exchange rate and production simultaneosuly and partially to the rubber export commodities in Indonesia since 1998 to 2015. This study used multiple time series regression analysis model PAM and for the hypothesis tested as the date analysis. The results of this study indicated that simultaneously inflation, exchange rate, and production amount significantly affect the rubber export commodities in indonesia. While, partially result of this research indicate that inflation and exchange does not have significant effect to rrubber commoditty export in Indonesia, but production amount have significant effect to the rubber export commodity in Indonesia.Keyword : Inflation, exchange rate, proudction, rubber export.